Aberration-corrected electron microscopy processing and imaging of novel organic and inorganic nanostructures - Nicolosi, V; Cosgriff, E; Coleman, J; Nellist, P (IOP Publishing, 2010)
One dimensional nanostructures such as organic and inorganic nanotubes, nanowires and graphene have generated much excitement among materials scientists in recent years. However difficulties associated with their lack of processability have seriously hampered the number of possible applications. Poor dispensability in most common solvents and tendency to bundle forming larger aggregates has been a hurdle in the way of real exploitation. The recent development of techniques able to disperse and exfoliate these 1D objects have captured much attention, strongly re-launching these materials towards the applicative scene. It is mandatory to understand at what extent these techniques are efficient and whether the atomic structures of these nanomaterials are damaged or remain pristine after dispersion and exfoliation in liquid media. Aberration-corrected electron microscopy becomes in this context a very attractive and unique tool to investigate these structures at atomic scale.